2019
DOI: 10.1093/ofid/ofz140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Empiric Anti–Mycobacterium tuberculosis Therapy on Survival Among Human Immunodeficiency Virus–Infected Adults Admitted With Sepsis to a Regional Referral Hospital in Uganda

Abstract: Background Mycobacterium tuberculosis is the leading cause of bloodstream infection among human immunodeficiency virus (HIV)–infected patients with sepsis in sub-Saharan Africa and is associated with high mortality rates. Methods We conducted a retrospective study of HIV-infected adults with sepsis at the Mbarara Regional Referral Hospital in Uganda to measure the proportion who received antituberculosis therapy and to determine the relationship between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…As a special case, a TB patient with severe sepsis can be administered with the empiric antituberculosis treatment. The WHO guidelines also support this strategy, calling for immediate instead of delayed empiric therapy in areas of high tuberculosis and HIV prevalence [ 109 ].…”
Section: Impact Of Treatment Optionsmentioning
confidence: 99%
“…As a special case, a TB patient with severe sepsis can be administered with the empiric antituberculosis treatment. The WHO guidelines also support this strategy, calling for immediate instead of delayed empiric therapy in areas of high tuberculosis and HIV prevalence [ 109 ].…”
Section: Impact Of Treatment Optionsmentioning
confidence: 99%
“…An expected lower proportion of patients with confirmed TB died before the two-week PK visit compared to those without microbiological confirmation of TB. While the high and early case fatality rate is not dissimilar to other cohorts with HIV and critical illness in Uganda [ 19 ], we were unable to determine if there were PK differences among those with early mortality and those who survived to PK testing. Given that the pathophysiology of severe sepsis leads to altered plasma drug binding capabilities and decreased drug perfusion to tissues, and impaired metabolism and clearance due to liver and kidney injury [ 18 ], it is possible that those patients with early mortality may have had unexpectedly higher serum exposures than were measured in the cohort of survivors.…”
Section: Discussionmentioning
confidence: 90%
“…Similar to the findings of the Klinger study, we also found that the UVA score calculated at 72 hours after admission performed less well than when calculated at admission. This difference in performance may be because improvement in vital signs in the short term do not necessarily predict improved outcomes in the long term due in part to immunodeficiency, poor nutrition, and a lack of appropriate antimicrobial therapy [ 17 19 ]. For example, in a study of the resuscitation of patients with sepsis in Uganda, we found that vital signs and whole blood lactate improved over the first 6 hours but that these improvements were not associated with improved case fatality rates [ 18 ].…”
Section: Discussionmentioning
confidence: 99%